Effect of Mass-Center Position of Spinal Segment on Dynamic Performances of Quadruped Bounding with a Flexible-Articulated Spine - Shun Zeng; Yuegang Tan; Zhang Li; Ping Wu; Tianliang Li; Junfeng Li; Haibin Yin (Applied Sciences, 2020)
Driven by the layout design of devices arranged on the spine of quadruped robot which has a symmetry spine with a flexible joint, we explore the effect of mass-center position of spinal segment (MCPSS) on dynamic performances of quadruped bounding. A simplified model is introduced with MCPSS set as an independent parameter. Periodically quadruped bounding motions are generated to calculate different dynamic performances related to different MCPSS at the low, medium, and high horizontal speeds, respectively. The results indicate MCPSS corresponding to the optimal or suboptimal dynamic performances mainly gather at two positions: the hip joint and the geometric center of spinal segment. MCPSS near the hip joint leads to the largest stride period, stride length, and spinal oscillation-margin at all speeds. The smallest duty factor can also be obtained at the medium and high speeds. These improved inherent characteristics offer advantages in leg-orientation control and fast movement effectively. MCPSS near the geometric center of spinal segment brings the best self-stability, the smallest mass-center vertical fluctuation, and the smallest maximum foot-end force at all speeds, which should greatly enhance resistances to vertical jitters and reduce torque-demands of joint-drivers. This study should give useful suggestions to robot designs in reality.